2018
DOI: 10.1007/s11099-018-0812-x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition mitigates salinity stress in maize by modulating ion accumulation, photosynthesis, and antioxidants

Abstract: Silicon is known to improve resistance against salinity stress in maize crop. This study was conducted to evaluate the influence of silicon application on growth and salt resistance in maize. Seeds of two maize genotypes (salt-sensitive 'EV 1089' and salt-tolerant 'Syngenta 8441') were grown in pots containing 0 and 2 mM Si with and without 50 mM NaCl. After detailed investigation of ion concentrations in different maize organs, both genotypes were further selected in hydroponic experiment on basis of their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 35 publications
(66 reference statements)
2
22
0
Order By: Relevance
“…Likewise, Bosnic et al (2018) reported that the Na + concentration of Si-treated maize was higher than that found in Si-untreated plants after 14 days of salt stress, with Na + being sequestered into the vacuoles. In contrast, Khan et al (2018) showed reduced tissue levels of Na + in maize but the effect depended on both genotype and the plant organ and similar observations are plentiful in the literature ( Supplementary Table 2 ).…”
Section: Mechanisms Of Si-induced Drought and Salt Tolerancesupporting
confidence: 82%
See 1 more Smart Citation
“…Likewise, Bosnic et al (2018) reported that the Na + concentration of Si-treated maize was higher than that found in Si-untreated plants after 14 days of salt stress, with Na + being sequestered into the vacuoles. In contrast, Khan et al (2018) showed reduced tissue levels of Na + in maize but the effect depended on both genotype and the plant organ and similar observations are plentiful in the literature ( Supplementary Table 2 ).…”
Section: Mechanisms Of Si-induced Drought and Salt Tolerancesupporting
confidence: 82%
“…This paper ‘bucks the trend’ of Si-induced reductions in shoot Na + levels (e.g. Khan et al, 2018 for maize) and reported increased levels of leaf Na + . This makes it most likely that the changes in transcript level are due to altered Na + fluxes and concentrations, rather than a direct effect of Si, since there is good evidence for salt induced transcriptional regulation of SOS, HKT , and NHX .…”
Section: Contrasting Results From Omics Studiesmentioning
confidence: 75%
“…Salinity-induced water insufficiency and nutrient such as Ca 2+ , K + , Fe 2+ , and Zn 2+ deficiency within plants leads to photosynthesis disruption and oxidative stress [13]. Overall, salinity causes the reduction of leaf area, stomatal conductance, and chlorophyll levels in the plants [14] and promotes the generation of reactive oxygen species (ROS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Si is coming to the fore as a true “Cinderella” element (Artyszak, 2018), gaining interest among scientists from across the world because of its effective role in plant physiology, nutrition, and defense response. The valuable role of exogenous Si on plant growth and yield has been well-documented in the literature, but its true potential lies in the amelioration of abiotic and biotic stresses (Rodrigues and Datnoff, 2015; Khan et al, 2018; Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%